2014
DOI: 10.1038/labinvest.2014.71
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alpha-induced reduction of glomerular filtration rate in rats with fulminant hepatic failure

Abstract: The mechanism of renal failure during fulminant hepatic failure (FHF) or end-stage of liver disease is not fully understood. The present study aims to delineate the mechanisms of decreased glomerular filtration rate (GFR) in acute hepatic failure. A rat model of renal insufficiency in severe liver injury was established by lipopolysaccharide (LPS) plus D-galactosamine (GalN) exposure. GFR was evaluated by continuous infusion of fluorescein isothiocyanate-inulin with implanted micro-osmotic pumps. GalN/LPS into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Semi-quantitative Western blot analysis demonstrated that IP 3 RI protein expression was low in normal kidney tissue. Following treatment with D-GalN plus LPS, IP 3 RI protein expression began to rise at 3 h and reached a peak at 12 h. Interestingly, liver and kidney dysfunction and hepatocyte necrosis were most severe and blood TNF-α and ET-1 levels were highest at 12 h, which were concomitant with the elevation of IP 3 RI protein expression in the kidney[ 42 , 43 ]. By treating the animals with D-GalN or LPS alone, we excluded the effect of these drugs on IP 3 RI protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Semi-quantitative Western blot analysis demonstrated that IP 3 RI protein expression was low in normal kidney tissue. Following treatment with D-GalN plus LPS, IP 3 RI protein expression began to rise at 3 h and reached a peak at 12 h. Interestingly, liver and kidney dysfunction and hepatocyte necrosis were most severe and blood TNF-α and ET-1 levels were highest at 12 h, which were concomitant with the elevation of IP 3 RI protein expression in the kidney[ 42 , 43 ]. By treating the animals with D-GalN or LPS alone, we excluded the effect of these drugs on IP 3 RI protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, there was a significant histopathological alteration in the Gal- treated rats. The livers extensively displayed diffuse coagulative necrosis [ 35 , 71 ]. In the same line, the kidneys revealed congestion in the blood vessels, glomeruli associated with perivascular oedema, inflammatory cells infiltration, degeneration in the lining epithelium of the tubules and focal haemorrhage in the corticomedullary portion due to the elevated level of ROS and the upshot of pro-inflammatory cytokines [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of FHF and treatments in different groups. FHF was induced in rats using a combination of GalN (400 mg/kg) plus LPS (32 g/kg) in saline, administrated through tail vein at a volume of 2 ml/kg 2 wk after lentiviral injection and 7 days after intraperitoneal implantation of micro-osmotic pumps (29). Rats with the implantation of 2 micro-osmotic pumps were randomly divided into four groups 1) N.S.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, these rats exhibited a similar trend of increased plasma TNF-␣ and ET-1 levels. Pretreatment with anti-TNF-␣ antibody significantly improved renal function and GFR (29). TNF-␣ treatment led to an increase in IP 3 R1 expression; in turn, enhanced IP 3 R1 expression amplified the sensitivity of GMCs and VSMCs in response to a variety of vasoconstrictors, thus leading to contraction of these two cell types and resulting in reduced GFR.…”
Section: Introductionmentioning
confidence: 97%